Implementation of the Role of Nurses as Advocators for Patients in the Class III - Aeni, Qurrotul; Lutvianti, Lutvianti; Anggraeni, Rina; Nurwijayanti, Andriyani Mustika (Global Health Science Group, 2025)
The advocate is an act by the nurse to defend and protect the rights of the patient, to improve what is best for the patient, to meet the patient’s need. Implementation of the nurse’s role as advocate is very important for the patient. This study aims to know the description of the implementation of the role of nurse as advocates in patient. This research uses quantitative method with decriptive observational research design and approach is done by survey. The sample in this research were 242 patients in the class III inpatient room at Soewondo Kendal hospital using proportional stratified random sampling of 611 population. Research shows that the implementation of the role of nurse as an advocate on this patient has been done fairly well. Can be concluded that the implementation of the role of nurse as an advocate in patients in Soewondo Kendal hospital has been implemented with good results. Based on the results of research, it is advisable for hospitals to maintain service and improve the quality of good service with always respect the right of patients. Hospitals are expected to conduct training or seminars for nurses about the role of advocates in patients.